New 24-Membered Macrolactines from an Arctic Bacterium Bacillus amyloliquefaciens SCSIO 41392 and Their Anti-Pathogenicity Evaluation - Yue Song; Yachun Zhou; Mengjing Cong; Shengyi Deng; Yushi Chen; Xiaoyan Pang; Yonghong Liu; Li Liao; Liang Yang; Junfeng Wang (Marine Drugs, 2024)
Three new 24-membered macrolactines, amylomacrolactines A–C (1–3), along with two known compounds 4 and 5, were isolated from the Arctic bacteria Bacillus amyloliquefaciens SCSIO 41392. The configurations of 1–3 were assigned by a combination of coupling constants, NOESY, and analysis of MM2-optimized conformation, as well as by comparison with reports in the literature. Compounds 1 and 2 showed quorum sensing (QS) inhibitory activities against the Pseudomonas aeruginosa (P. aeruginosa) PQS system and suppressed PQS-regulated virulence factor pyocyanin synthesis. In addition, compounds 3–5 affected the production of another essential virulence factor, siderophore of pyoverdine (PVD), in P. aeruginosa. More importantly, compound 5 showed an anti-biofilm activity against P. aeruginosa. Altogether, the isolated compounds displayed multiple bacterial virulence inhibition activities, which is worthy of further exploration for novel analogues in antimicrobial drug development.